Hesitancy of COVID-19 vaccine in a working-age population in a town in Central Maharashtra in Western India: A survey based on vaccine characteristics. (March 2022) - Sayed, M.A.; Syed, H.; Guru, N.K.; Nazneen, S.; Sayed, S.A.
Abstract : Purpose: Assessments of public sentiments and opinion polls on vaccinations recommend that COVID-19 vaccine hesitancy is globally expanding; nonetheless, the usefulness of opinion polls to plan mass vaccination campaigns for vaccines and to gauge acknowledgment in a country's populace is restricted. Hence, we aimed to evaluate the impacts of vaccine characteristics, information on herd immunity, and general medical practitioner (GP) recommendation on vaccine hesitancy in a working-age population in Kolhapur, a town in Central Maharashtra in Western India. Methods & Materials: In this survey, adults aged 18-64 years residing in Kolhapur, with no history of SARS-CoV-2 infection, were randomly selected in April-2021. Participants completed a questionnaire on their background and vaccination behavior-related variables, and were then randomly assigned according to a full factorial design to one of three groups to receive differing information on herd immunity and to one of two groups regarding GP recommendation of vaccination. Participants then completed a series of eight discrete choice tasks designed to assess vaccine acceptance or refusal based on hypothetical vaccine characteristics, risk of serious side-effects, location of manufacture, and place of administration. Responses were statistically analyzed. Results: Responses were collected from 843 working-age adults, of whom 163 (19.33%) opted for no vaccination (outright vaccine refusal) and 680 (80.66%) did not. Here, outright vaccine refusal was associated with a lower perceived severity of COVID-19, whereas vaccine hesitancy was lower when herd immunity benefits were communicated and in working versus non-working individuals, and those with experience of COVID-19. For a mass vaccination campaign involving mass vaccination centers and communication of herd immunity benefits, our results predicted outright vaccine refusal in 23.6% (95% CI 197-284) of the Kolhapur working-age population. Predicted hesitancy was highest for vaccines manufactured in China with 50% efficacy and a 1 in 10, 000 risk of serious side-effects (vaccine acceptance 274% [268-280]), and lowest for a vaccine manufactured in the USA with >90% efficacy and a 1 in 1, 00, 000 risk of serious side-effects (vaccine acceptance 736% [69.6-781]). Conclusion: COVID-19 vaccine acceptance depends on the characteristics of vaccines and the national vaccination strategy, amongst various other factors, in the working-age population in Kolhapur.